Discurso y Sociedad: Una nueva revista digital - van Dijk, Teun A. (Discurso & Sociedad, 2007)
<span style="color: #333333; font-family: 'Helvetica Neue', Helvetica, Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Discurso y Sociedad: Una nueva revista digital.